Implementation of early warning, alert and response: An experience from the Marburg virus disease outbreak response in Kagera, Tanzania, March to May 2023. - Atuganile Musyani; Emmanuel Mwakapasa; Marcelina Mponela; Lusungu Ngailo; Irene Rabiel; Mwanakombo Khama; Eninka Mmbaga; Calvin Sindato; Mololo Noah; Werema Solomon; George Mrema; Danstan Ngenzi; et al. (PLoS ONE)
Introduction Tanzania declared a Marburg Virus Disease (MVD) outbreak on March 21, 2023, reporting nine cases and six deaths (case fatality rate (CFR) 66.7%). Detection began when a Community Health Worker (CHW) reported unexplained illness via the electronic EBS (e-EBS) system, triggering a national outbreak response. This study documents the Early Warning, Alert and Response (EWAR) interventions carried out during the MVD outbreak response in the Kagera region to identify strengths and bottlenecks for strengthening future outbreak preparedness and response efforts. Method We documented EWAR interventions using retrospective surveillance document review. MVD outbreak detection and reporting timeliness were compared with Tanzania's EBS indicators and the 7-1-7 target. Surveillance interventions included additional staff deployment, equipment addition, and tool adoption. Community sensitization efforts utilized Swahili-translated informational cards to facilitate early detection and reporting of signals through multiple channels, including the 199-hotline number, EBS desk numbers and via e-EBS and verified using the standard case definition (SCD). Signals were compiled in Microsoft Excel, where descriptive analysis using frequencies to show trends was conducted. Suspected MVD cases were sent for laboratory confirmation. Findings On March 15, 2023, a CHW reported a signal in the e-EBS system within 24 hours. However, a community member and HCWs missed unusual signs of the MVD index case. Five additional members were deployed to support data management using the equipment provided, including three laptops, ten smartphones, and adapted tools. A total of 6,260 informational cards were distributed during community sensitization; 176 MVD signals were reported, where 48 (27.3%) met the SCD, and 37 were sent for laboratory confirmation, of which 2.7% tested positive for the virus. Most signals, 107 (60.8%), were reported in April. Conclusions and recommendations The government should adopt the 7-1-7 target and strengthen community and health facility EBS through ongoing mentorship for EWAR.